The current news of the Frankfurt perspective for the challenges of inclusive education for an equanime world - Victor Hugo Oliveira Pinto (MLS Journals S.L., 2018)
This article deals with the analysis of Frankfurtrt's theorists, especially Adorno, Marcuse, Walter Benjamin and Horkheimer, and their relevance in relation to education. Motivation, faced with a world in which extreme-right values ​​and religious fundamentalisms are promoted, such a scenario motivates us to question the role that education plays in combating extremism and intolerance. Scope of relevance. This article is directly related to the philosophy of education. Justification and relevance. This topic is justified because it deals with teleological aspects of the function of education. In the sense of questioning the teleological character of education based on philosophical concepts that seek the autonomy of the subject instead of just the human being to what is settled. As a methodology, it resorts to bibliographical studies and critical reflections on education and its political character in the construction of an emancipated social conscience of values ​​that legitimize oppression. Results and discussion. A study on Critical Theory of Adorno, Horkheimer, Benjamin, Habermas and Marcuse was conducted as contributions to the construction of an education that, in addition to seeking inclusion, also seeks to be a political instrument to combat prejudice, which is nowadays alive again with the rise of religious fundamentalisms, xenophobia and the rise of extreme-right political ideas. Conclusion. It is concluded that the school has the political purpose to educate for a world of solidarity and respect for differences.